Sustainable housing practices in housing development in Malaysia towards establishing sustainability index - Bakar, Abu Hassan Abu; Khor , Soo Cheen (2008)

(untitled)
This paper present the housing development processes aimed at applying sustainability principles specific in Malaysia context by drawing the experiences from exemplar projects in other countries and comparing them with the development needs under local conditions. The complexities of the projects do require compliances of project management best practices to achieve the goal of sustainable housing development. At the same time, this research is to identify the project critical success factor for application in the project management implementation in term of best practice to realize the goal of sustainable housing development. Sustainability Index is established with purpose to generated values into figures for the sustainable housing development that are used to characterize or evaluate specific aspects of the system through the assessment of housing sustainability indicators. The formula of sustainability index in housing development will be established accordingly. The parameters or variables based on the identifiable indicators of the success factors will be established with reference to the designed and practices of the green building rating system that had been adopted in Japan, United Stated, United Kingdom and other countries.